Made in Quebec, Reviewed in Toronto: Critical Response to Translated Quebec Theatre - Koustas, Jane (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractThe author studies the reception of Quebec plays in Toronto between 1970 and 1982. She compares the response of different critiques, focussing on analyses of translations and translators. The author shows that critics are guilty of being "Toronto-centric" by ignoring the importance of translation or seeking more easily understandable translations for Toronto audiences.